Dampak Penggunaan Media Pembelajaran Berbasis Teknologi Terhadap Siswa di SMKN 7 Kota Serang : Studi Kasus Kelas X RPL - Guslan Isnenshah; Faiza Amanda Chairunisa; Ananda Yhuto Wibisono Putra; Siti Robiah; Triyo Susanto (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research aims to examine the impact of using technology-based learning media on class X Software Engineering (RPL) students at SMKN 7 Serang City. In the ever-growing digital era, technology has become an important part of education, offering various forms of learning media that are more interactive and interesting. This research uses a qualitative approach with a case study method to explore the challenges and impacts of using technology-based learning media on student learning outcomes. Data collection techniques were carried out through literature studies, interviews and direct observation. The research results show that the use of technology-based learning media can improve the quality of learning and understanding of the material by students, as well as motivate them to be more active in learning. Media such as digital tutorials, e-learning, and simulations allow students to learn independently and gain practical skills relevant to the world of work. However, there are significant challenges, such as limited technological facilities and gaps in access between students who have devices and those who do not. Therefore, efforts are needed to improve technological facilities and equalize access for all students. This research contributes to understanding the role of technology in education, especially at SMKN 7 Serang City, as well as providing recommendations for maximizing the implementation of technology-based learning media in vocational education in Indonesia.